Recent advances in ZBP1-derived PANoptosis against viral infections - Oh, SuHyeon; Lee, SangJoon (Frontiers in Immunology, 2023)
Innate immunity is an important first line of defense against pathogens, including viruses. These pathogen- and damage-associated molecular patterns (PAMPs and DAMPs, respectively), resulting in the induction of inflammatory cell death, are detected by specific innate immune sensors. Recently, Z-DNA binding protein 1 (ZBP1), also called the DNA-dependent activator of IFN regulatory factor (DAI) or DLM1, is reported to regulate inflammatory cell death as a central mediator during viral infection. ZBP1 is an interferon (IFN)-inducible gene that contains two Z-form nucleic acid-binding domains (Zα1 and Zα2) in the N-terminus and two receptor-interacting protein homotypic interaction motifs (RHIM1 and RHIM2) in the middle, which interact with other proteins with the RHIM domain. By sensing the entry of viral RNA, ZBP1 induces PANoptosis, which protects host cells against viral infections, such as influenza A virus (IAV) and herpes simplex virus (HSV1). However, some viruses, particularly coronaviruses (CoVs), induce PANoptosis to hyperactivate the immune system, leading to cytokine storm, organ failure, tissue damage, and even death. In this review, we discuss the molecular mechanism of ZBP1-derived PANoptosis and pro-inflammatory cytokines that influence the double-edged sword of results in the host cell. Understanding the ZBP1-derived PANoptosis mechanism may be critical for improving therapeutic strategies.